Playing an Augmented Reality Escape Game Promotes Learning About Fake News - Buchner, Josef (Technology, Knowledge and Learning, 2024)
The spread of fake news poses a global challenge to society, as this deliberately false information reduce trust in democracy, manipulate opinions, and negatively affect people’s health. Educational research and practice must address this issue by developing and evaluating solutions to counter fake news. A promising approach in this regard is the use of game-based learning environments. In this study, we focus on Escape Fake, an augmented reality (AR) escape game developed for use in media literacy education. To date, there is limited research on the effectiveness of the game for learning about fake news. To overcome this gap, we conducted a field study using a pretest-posttest research design. A total of 28 students (14 girls, mean age = 14.71 years) participated. The results show that Escape Fake can address four learning objectives relevant in fake news detection with educationally desired effect sizes: Knowledge acquisition (d = 1.34), ability to discern information (d = 0.39), critical attitude toward trustworthiness of online information (d = 0.53), and confidence in recognizing fake news in the future (d = 0.41). Based on these results, the game can be recommended as an educational resource for media literacy education. Future research directions are also discussed.
Keywords: Augmented Reality